Participation in Sports Teams and Suicidal Behavior: An Analysis of the 1995 National College Health Risk Behavior Survey. Issue 1 (August 2014) - Lester, David
A 1995 data set from a survey of college students carried out by the Centers for Disease Control was examined to explore whether participation in sports was associated with recent suicidal behavior. Overall, participation in college sports was associated with a reduced incidence of suicidal ideation in the past year, but had no association with attempted suicide in the past year. However, this protective effect was found for European American students, Hispanic Americans, and Asian Americans, but not for African Americans, and was stronger for male students than for female students.